Quantum Optimization for Enhanced Combinatorial Algorithms - Pandey, Pradeep Kumar; Chaturvedi, Ruchi; Dangi, Suraj Bhan (The Nucleus, 2025)
The twenty-first century has been the era of data. Algorithms are crucial in tasks ranging from simple document searches to complex batching and scheduling jobs. Optimization techniques are often applied to enhance algorithms and achieve better results. As Moore rightly predicted, the exponential increase in transistors has led to a point where classical computers can no longer solve specific problems within a human timeframe. This paved the way for the development of quantum computers, which utilize quantum phenomena to solve problems. Quantum optimization techniques and algorithms have been designed to leverage the quantum advantage for improved optimization. This research compares and presents the results of quantum optimization techniques applied to classic combinatorial algorithms.